Knowledge of The Health Volunteer Team About Basic Life Support (BLS) At Indonesia University of Education - Upik Rahmi; Afianti Sulastri (Universitas STRADA Indonesia, 2020)
The purpose of this research is to find out the knowledge of the Health Corps Volunteer Team of the Indonesian Education University about basic life support. Research design with the quantitative descriptive approach, sampling with a total sampling of 60 respondents. Results showed the respondents' knowledge into 2 categories: 46 participants (76.67%), enough 14 participants (23.33%) while there were no respondents. Knowledge is influenced by several factors; some are based on gender, age and the faculty of study. Knowledge of important basic living rocks is given to students in addition to health. Suggestions for increasing knowledge and training on basic life support with the aim of numbers helps to reduce mortality